Validating ICD-10 Diagnosis Codes for Guillain-Barré Syndrome in Taiwan’s National Health Insurance Claims Database [Letter] - Seha HN; Budi SC; Noor AY; Pradnyantara IGANP (Clinical Epidemiology)
Harinto Nur Seha,1 Savitri Citra Budi,2 Ahmad Yani Noor,3 I Gusti Agung Ngurah putra Pradnyantara4 1Medical Record and Health Information Department, Poltekkes Permata Indonesia, Yogyakarta, Indonesia; 2Department of Health Information and Services, Vocational School, Universitas Gadjah Mada, Yogyakarta, Indonesia; 3Hospital Administration, Poltekkes Permata Indonesia, Yogyakarta, Indonesia; 4Medical Record and Health Information Department, STIKES Wira Medika, Bali, IndonesiaCorrespondence: Harinto Nur Seha, Poltekkes Permata Indonesia Yogyakarta, Jl. Ringroad utara No. 22C, Condongcatur, Depok, Sleman, Daerah Istimewa, Yogyakarta, Indonesia, Email harinto_ns@permataindonesia.ac.id